Kemampuan Berargumentasi Siswa Melalui Pendekatan Saintifik pada Jenjang SMA dengan Tingkat Akreditasi yang Berbeda di Lampung Utara - Anitia Fadhila Bumay; Neni Hasnunidah; Dina Maulina (BIOEDUSCIENCE, 2022)
Background: Argumentation skill is a crucial ability to be possessed by students. Argumentation skills can be trained by applying a scientific approach during learning. The implementation of the scientific approach in schools can vary; it is suspected that one of the causes is the accreditation rating. The study aimed to determine the differences in the argumentation skill of high school students based on their accreditation rating. Methods: The research design used is the Ex-post Facto design. The sample in this study was sampled using the purposive sampling technique. Results:  There are differences in students' argumentation abilities between accreditation ratings of A, B, and C. Conclusions: Students' argumentation skill differs between high school students with accreditation ratings of A, B, and C. The difference in students' argumentation skills is caused by differences in the application of the scientific approach applied by teachers in each school.